2014
DOI: 10.1039/c3mb70414a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore genes are required to fully activate secretory pathway expansion in S. cerevisiae under induced ER stress

Abstract: Basal ER stress occurs when proteins misfold in normal physiological conditions and are corrected by the unfolded protein response (UPR). Elevated ER stress occurs when misfolding is refractory as found in numerous diseases such as atherosclerosis, Type II diabetes and some cancers. In elevated ER stress it is unclear whether cells utilise the same or different networks of genes as in basal levels of ER stress. To probe this question, we used secretory pathway reporters Yip3p-GFP, Erv29p-GFP, Orm2p-GFP and UPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The EMC complex use per se is worthy of comment because in S288C subunits individually have an effect on intracellular traffic 38 and it is possible the number of subunits used are proportional to ER stress in S288C compared to the statin-resistant strains. Thirdly, induced ER stress requires secretory pathway gene interactions with kinetochore genes 60 and here we detected the COMA complex (Ctf19p, Okp1p, Mcm21p and Ame1p) for atorvastatin and cerivastatin response in all genetic backgrounds (except YPS606 in cerivastatin) in one specific community (Supplementary Table S9). Fourthly, we demonstrated that UPR-specific communities containing CWH41, IRE1 and/or HAC1 had different complements of other UPR-related genes depending on genetic background and also on whether the statin drug was atorvastatin or cerivastatin.…”
Section: Discussionmentioning
confidence: 60%
“…The EMC complex use per se is worthy of comment because in S288C subunits individually have an effect on intracellular traffic 38 and it is possible the number of subunits used are proportional to ER stress in S288C compared to the statin-resistant strains. Thirdly, induced ER stress requires secretory pathway gene interactions with kinetochore genes 60 and here we detected the COMA complex (Ctf19p, Okp1p, Mcm21p and Ame1p) for atorvastatin and cerivastatin response in all genetic backgrounds (except YPS606 in cerivastatin) in one specific community (Supplementary Table S9). Fourthly, we demonstrated that UPR-specific communities containing CWH41, IRE1 and/or HAC1 had different complements of other UPR-related genes depending on genetic background and also on whether the statin drug was atorvastatin or cerivastatin.…”
Section: Discussionmentioning
confidence: 60%
“…The non-canonical RBP Bfr1p is involved in several cellular processes including transfer and 123 retention of mRNAs to P-bodies (Simpson et al 2014;Weidner et al 2014), translation (Lang 124 et al 2001), and response to functional failure of the yeast spindle pole body or kinetochore 125 (Sezen et al 2009;Low et al 2014). We generated bfr1 mutants in order to address the 126 question of whether RNA-binding is required for all processes.…”
Section: Rna-binding Of Bfr1p Is Required For Its Localization To Thementioning
confidence: 99%
“…In yeast, it is associated with over 1,000 different mRNAs, enriched for those encoding ribosomal proteins and mRNAs that are translated at the ER (Lapointe et al, 2015). In addition to a role in stress granules, Bfr1 has been implicated in ER quality control (Low et al, 2014) and correct nuclear segregation (Xue et al, 1996). The physical interaction map (https://www.yeastgenome.org/locus/S000005724/interaction) includes five proteins related to mRNA decay: with Xrn1p, Dcp2p, Scp160p, Puf3p, and Asc1p (an orthologue of RACK1 that inhibits translation).…”
Section: Introductionmentioning
confidence: 99%